Design, Molecular Modeling and Synthesis of Some New Purine-diones and Pyridopyrimidine-diones with Anticancer Activity - Hayallah, Alaa M. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
An olomoucine analogues of 2-[(1-substituted)-2,6-dioxo-2,3,6,7–tetrahydro-1H-purin-8-ylsulfanyl]-N-substituted acetamide 6a-g and 7a-g, 1-substituted-8-[2-(4-substituted phenyl)-2-oxoethylsulphanyl]-3,7-dihydro-1H-purine-2,6-diones 9a-g and 10a-g, 3-(2-substituted benzyl)-6-(4-substituted phenyl)-1H-thiazolo[2,3-f]purine-2,4-dione 11a-g and 12a-g and their isosteres 3-substituted benzyl-5-methyl-7-substituted-1H-pyrido[2,3-d]pyrimidine-2,4-dione 13a-c and 14a-c were designed and synthesized. The target compounds 11a-g and 12a-g were prepared by cyclodehydration of 9a-g and 10a-g in PPA, while 13a-c and 14a-c were synthesized by condensation of 6-amino-3-(2-substituted benzyl)-1H-pyrimidine-2,4-dione 1a or 1b and the appropriate acylacetone in glacial acetic acid. Structures of the new compounds were verified on the basis of their IR, 1H NMR, MS, HRMS and elemental analyses. The newly synthesized compounds were tested for their anticancer activity and most of the tested compounds showed good to excellent inhibition activity against the tested human breast cancer cell line MCF-7 in comparison to doxorubicin as a reference drug. KEYWORDS: olomoucine; cyclin-depenent kinase; synthesis; anticancer